Electrophysiological Characterization of eGFP-Labeled Intrastriatal Dopamine Grafts. Issue 8 (August 2015) - Hohmann, Meltem; Rumpel, Regina; Fischer, Martin; Donert, Malte; Ratzka, Andreas; Klein, Alexander; Wesemann, Maike; Effenberg, Anna; Fahlke, Christoph; Grothe, Claudia
Substitution of degenerated dopaminergic (DA) neurons by intrastriatally transplanted ventral mesencephalon (VM)-derived progenitor cells has been shown to improve motor functions in parkinsonian patients and animal models, whereas investigations of electrophysiological properties of the grafted DA neurons have been rarely performed. Here we show electrophysiological properties of grafted VM progenitor cells at different time intervals up to 12 weeks after transplantation measured in acute brain slices using eGFP-Flag transfection to identify the graft. We were able to classify typical DA neurons according to the biphasic progression (voltage "sag") to hyperpolarizing current injections. Two types of DA-like neurons were classified. Whereas type 1 neurons were characterized by delayed action potentials after hyperpolarization and irregular spontaneous firing, type 2 neurons displayed burst firing after hyperpolarization, spontaneous bursts, and regular firing. Comparison to identified DA neurons in vitro indicates a high integration of the intrastriatally grafted neurons, since in vitro cultures displayed regular firing spontaneously, whereas grafted identified DA neurons showed irregular firing. Additionally, type 1 and type 2 neurons exhibited a slight increase in the spontaneous firing frequency over time intervals after grafting, which might reflect a progressive integration of the grafted DA neurons. Our results provide evidence of the differentiation of grafted VM progenitor cells into mature integrated DA neurons, which are shown to replace the missing DA neurons functionally early after grafting.